Management Analysis Syariah at UMKM in Gresik - Khakim, M. Azizul (JIM: Jurnal Ilmiah Mahasiswa Pendidikan Sejarah, 2023)
This study provides an overview of regarding the implementation of sharia management for MSMEs in the Gresik area. MSMEs are now in a position to begin to understand business and managerial principles, so that these two things can influence the business development of these MSMEs. Sharia management does not only discuss managerial or Islamic economic principles, but is broader than that. Islamic management provides a broader and more critical view of SMEs to be more aware of business values and principles more accurately and critically. As well as working with the ethics and rules that Islam has prescribed. This research will produce outputs related to the role of sharia management and MSMEs in the Gresik area.